INTEGRASI ANTARA INTERIOR DESAIN DAN GRAFIS INTERIOR PADA INTERIOR KANTOR POLYTRON DI SURABAYA - Ivelin Marva Wirahadikusumah; Freddy Handoko Istanto; Rani Prihatmanti (Universitas Ciputra Surabaya, 2016)
Nowadays, the growth of human population and economy is increasing more rapidly than in the previous years. Those factors have given positive impact on the increasing of property development such as residential and commercial projects. Because of the increasing of property development, interior designers are required to make a good interior design so it can function well and solve space or interior problems correctly and also give a good esthetic look to each and every project given. By this case, iVEL_ Qing Interior Design Consultant is presenting an interior design firm with interior graphic application as the added value. The interior graphic design application service is used to strengthen the design character/ design by implicating graphic design on walls, ceiling and floor or even interior products. Referring to the added value of iVEL_Qing Interior Design Consultant, Polytron office interior project is selected to be the study case because the existing condition that has not reflected the character or signature of the company’s brand. To solve the design problem, iVEL_Qing Interior Design Consultant is giving the right solution by designing the interior focused on space planning, circulation, air quality and both interior design style especially, that it is supported by the interior graphic design application service from iVEL_Qing Interior Design Consultant itself.